MENINGKATKAN PEMAHAMAN PANCASILA PADA SISWA KELAS II SD MELALUI BAHAN AJAR DIGITAL GOOGLE SITES - Moh.Fuad Agil Mustofa; Frans Aditia Wiguna; Kharisma Eka Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop teaching materials based on Google Sites for the topic "the meaning of symbols and the implementation of the principles of Pancasila" for second-grade students at SDI Darus Sholihin. The background of this research is the lack of engaging learning media, which leads to students being passive during learning activities. The development model used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The results show that the developed teaching materials are valid (88%), practical (95%), and effective (88%) in improving students' understanding. These materials are considered suitable as an interactive and enjoyable digital learning medium.